Restructuring and quality : issues for tomorrow's schools - Townsend, Tony (Educational management series., 1997)
The worldwide restructuring of the education system is causing major difficulties at a state level and for individual schools. The book aims to look at the linkages between this restructuring movement and the qualitative improvement it brings.